P04.01.B High impact of ITGB1 on Pi3K/AKT expression in medulloblastoma. (5th September 2022) - Zhu, S; Cheng, Z; Wu, Z; Wang, J
Abstract: Medulloblastoma, an embryonal tumor of the cerebellum, is one of the most frequent malignant brain tumors. Despite the increasing use of genetic variation in treatment stratification, high-risk patients characterized by light meningeal spread, TP53 mutations, or MYC amplification still have poor survival. Phosphatidylinositol-3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) signaling is one of the most important intracellular pathways, which can be considered as a master regulator for cancer. In tissue samples obtained from medulloblastoma patients, the significant upregulation of PI3K/AKT was associated with a lifting expression level of integrin β1(ITGB1). To understand the underlying mechanism, we investigated the effect of ITGB1 on the PI3K/AKT pathway in medulloblastoma cell lines. Transfection of this ITGB1 reduced proliferation and invasion of several medulloblastoma cell lines and inhibit epithelial-mesenchymal transition. In addition, knocking down ITGB1 expression can significantly inhibit the activation of PI3K/AKT signaling pathway. In conclusion, ITGB1 may selectively activation the pathophysiological effect of aberrant PI3K/AKT expression and serve as a targeted approach for medulloblastoma therapy.